PROCESS OPTIMISATION FOR READY TO EAT TAPIOCA (Manihot esculenta crantz) IN HIGH IMPACT POLYPROPYLENE CONTAINERS - Dinakaran, Ammu; C.O, Mohan; Panda, Satyen Kumar; Ravishankar, C.N; Gopal, T.K Srinivasa (JOURNAL OF ROOT CROPS, 2017)
Tapioca is a traditional food and is considered as a delicacy in Kerala when taken along with fish curry. Edible tapioca was blanched in 0.1% guar gum and packed in HIPP containers by hot filling the brine solution. Dynopack sealing machine was used for sealing the top of HIPP trays using polyester coated with silicon dioxide/ nylon/cast polypropylene. They were processed in still water immersion retort at 121.1 °C for different F0 values of 5, 6, 7 and 8 minutes. Based on the results of sensory evaluation and tests for commercial sterility an F0 value of 7 was optimised for the product. Upon thermal processing significant decrease (P<0.05) in hardness and chewiness was observed for tapioca.